Reflections on the Nature of an Urban Bog - Hermansen, Sally; Wynn, Graeme (Urban History Review / Revue d'histoire urbaine, 2005)
Camosun Bog has existed for approximately two thousand years. Little is known about its use by indigenous people, but it was left essentially undisturbed by European newcomers until the twentieth century. Then, as the population of Vancouver and its neighbouring suburb of Point Grey (amalgamated with Vancouver in 1929) grew almost exponentially, the bog was subject to massively accelerated change. By 1980 it was a tiny, endangered remnant landscape, little understood, and valued even less, until a small group of volunteers constituting the Camosun Bog Restoration Society began to reverse the ravages of the previous seventy-five years. This paper combines careful Geographical Information Systems–based mapping of the bog, using evidence from aerial photographs, the scientific findings of botanists, and interviews with members of the Bog Restoration Society, with research in the City of Vancouver archives and newspaper files to detail the effects of human action upon the bog and to reflect upon what the history of this unique place reveals about changing attitudes toward nature in the city.